1989
DOI: 10.1111/j.1365-2125.1989.tb03429.x
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐hepatic metabolism of midazolam.

Abstract: Six patients received 10 mg of midazolam intravenously during the anhepatic period of liver transplantation. Arterial blood was sampled during this time and for a similar period following revascularisation. The plasma was analysed using gas chromatography and electron capture detection (GC-ECD) for midazolam a-hydroxymidazolam and ahydroxymidazolam glucuronide. Five of the six patients had small but significant concentrations of metabolites detected during the anhepatic period, demonstrating the presence of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The findings that the intestinal extraction of midazolam was on average less than 10% in anhepatic liver transplant patients (173) and that the formation of midazolam's 1 -hydroxy metabolite was limited following intravenous administration in such patients (179) are supportive of this assumption, at least with this CYP3A substrate. Thus, midazolam's hepatic extraction ratio was estimated based on knowledge of liver blood flow, and the contribution of intestinal extraction to the overall first-pass effect following oral administration was determined (180).…”
Section: Route Of Administrationmentioning
confidence: 69%
“…The findings that the intestinal extraction of midazolam was on average less than 10% in anhepatic liver transplant patients (173) and that the formation of midazolam's 1 -hydroxy metabolite was limited following intravenous administration in such patients (179) are supportive of this assumption, at least with this CYP3A substrate. Thus, midazolam's hepatic extraction ratio was estimated based on knowledge of liver blood flow, and the contribution of intestinal extraction to the overall first-pass effect following oral administration was determined (180).…”
Section: Route Of Administrationmentioning
confidence: 69%
“…This method exploits the time period during transplant surgery when the patient's diseased liver has been removed and before the new organ has been introduced [9,11,29]. A value of F G is estimated from the difference in the AUC after duodenal administration of drug during this time period (when the contribution of the liver to clearance is absent) with the AUC after the same dose given when the liver is in place (when clearance is both hepatic and intestinal).…”
Section: Use Of Anhepatic Patientsmentioning
confidence: 99%
“…Moreover, there is a lesser degree of midazolam protein binding in patients with advanced hepatic disease, with a subsequent increase in the free fraction of the drug and enhancement of the pharmacologic effect. However, Trouvin et al 11 demonstrated only slightly impaired disposition in cirrhotic patients, and Park et al 12 described the presence of extrahepatic sites of metabolism for midazolam. In our study, this drug was administered only as co-inductant.…”
Section: Discussionmentioning
confidence: 97%